2021
DOI: 10.5114/ada.2020.97072
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of gentamicin 0.3% solution of oral erosions healing in patients with severe generalized recessive dystrophic epidermolysis bullosa and its impact on the expression of type VII collagen

Abstract: Introduction: Epidermolysis bullosa (EB) is a rare genetic skin disorder inherited either in autosomal recessive (AR) or autosomal dominant (AD) manner and characterized by blistering of the skin and mucous membranes. According to a subtype of EB, the oral manifestations and dental involvement vary in frequency and in severity. The most severe dental problems occur in patients with junctional epidermolysis bullosa (JEB) and severe generalized dystrophic epidermolysis bullosa (RDEB) and involve enamel erosion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Another study on four RDEB patients demonstrated the effect of a gentamicin 0.3% solution on oral erosions 92 . Immunofluorescence confirmed the partial re‐expression of type VII collagen.…”
Section: Ongoing and Completed Scr Clinical Trials In Ebmentioning
confidence: 86%
“…Another study on four RDEB patients demonstrated the effect of a gentamicin 0.3% solution on oral erosions 92 . Immunofluorescence confirmed the partial re‐expression of type VII collagen.…”
Section: Ongoing and Completed Scr Clinical Trials In Ebmentioning
confidence: 86%
“…81 In EPD processing, GS has been investigated in coatings for orthopedic implants, primarily for the treatment/prevention of periprosthetic infections. 23,82,83 Furthermore, GS has also been reported for the treatment of infections affecting mucosal tissues (e.g., oral mucosa 84 and nasal mucosa 85 ). Thus, the idea of this work was to combine this information to obtain, via a one-pot process, GS-loaded patches for the treatment of infections affecting oral mucosal tissues.…”
Section: Evaluation Of Gs Loading and Release For The Cs-mc Patchesmentioning
confidence: 99%